American Myth Values In Our Town Play By Thornton Wilder (A Study Of Mythology) - Uup Gufron (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2019)
This article aims to prove that American people really still believe in the myth during the early twentieth-century. The writer has found many historical data that support this research. In literary research he uses an analytic descriptive method. Finally, the collected data is explained and analyzed in order to answer the research problems. To support this research, he uses two theories; they are mythology theory and literary sociology approach.Thornton Wilder describes portrait of the American society that still believed in the myths in his best play entitled Our Town (1983). They lived in fictional small town namely Grover’s Corner. In their daily activities, they kept firmly the belief in the myths without missing the faith to religion. They realized that there were many positive things and goodness in every myth. The central values on the play are talking about three phases of life such as childhood, marriage and death.We find many myths about the childhood, marriage and death on the play. All they are talking about myths of days, months, weather, time, color, and ghost. In every belief of the myths, all of them contain how we can choose a good and bad one in facing problem. We should not do what the belief forbids. If we disobey them, -as in myth told- we will get some bad effect.